2019
DOI: 10.3390/bs10010014
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Marriages in Egypt: Impact of Divorce on Women

Abstract: Divorce rates have been increasing around the world, and the Middle East is not immune to this reality. This pilot study investigates the phenomenological experiences of divorce for 20 Egyptian females. The study is qualitative, using in-depth interviews asking 14 questions that address different aspects of struggling marriages and post-divorce life. Five main themes were derived using a conventional approach to content analysis. The themes are: Expectations before marriage, secret life, relational dynamics, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…The study showed that the ratio of males and females was close, as more than half of the participants were males (51%), which is consistent with the Egyptian population report for the year 2018, and this indicates that there was no genderspecific obstacle to participation. 11 The majority of the study subjects were married, and close to a quarter were widowed; usually, residents of rural areas tend to adhere to the presence of a partner, and so it becomes clear that most of the elderly are either married or even related to a partner; this is the result of the rural cultural inheritance in Egypt, which emphasizes the importance of the partner, and this agreed with the results of the research by Mendoza et al, 12 who explained that marriage in rural Egypt is an essential factor for seeking financial or social support, which is consistent with the results of this research. Also, most of the participants have children who take care of them in old age, which is one of the characteristics of the Egyptian countryside.…”
Section: Discussionsupporting
confidence: 78%
“…The study showed that the ratio of males and females was close, as more than half of the participants were males (51%), which is consistent with the Egyptian population report for the year 2018, and this indicates that there was no genderspecific obstacle to participation. 11 The majority of the study subjects were married, and close to a quarter were widowed; usually, residents of rural areas tend to adhere to the presence of a partner, and so it becomes clear that most of the elderly are either married or even related to a partner; this is the result of the rural cultural inheritance in Egypt, which emphasizes the importance of the partner, and this agreed with the results of the research by Mendoza et al, 12 who explained that marriage in rural Egypt is an essential factor for seeking financial or social support, which is consistent with the results of this research. Also, most of the participants have children who take care of them in old age, which is one of the characteristics of the Egyptian countryside.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the nature of the divorce process implies important effects on each of the above mentioned aspects simultaneously and at high intensity for a brief period of time (9 to 18 months). Consequently for women, divorce often implies the feeling of anxiety, helplessness, aggression, sadness, guilt, regret, shame, lack of self-esteem, emptiness, loneliness, and uncertainty about the outcome of divorce proceedings (Mendoza et al, 2019). In such a state of vulnerability, social judgement (especially strong in women with children) often converges with the divorce-seeking women's self-judgement, which leads into an internal battle of two contradictory thoughts of success, "I will become an independent human and be free" vs. failure, "I have not been able to continue my marriage and I'm responsible for it" (Gerstel, 1987).…”
Section: E) On the Cusp Of Sanity: Women Divorce Seekers And Mental H...mentioning
confidence: 99%
“…Numerous studies have examined the detrimental D E-ISSN: 2717-2430 effects of divorce, especially on women. Fear of the future, guilt, emotional and physical problems, role conflicts, social isolation and identity, and feelings of failure and defeat are among the negative effects of divorce on women (Mendoza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%